Damage modelling in concrete subject to sulfate attack - N. Cefis; C. Comi (Fracture and Structural Integrity)
In this paper, we consider the mechanical effect of the sulfate attack on concrete. The durability analysis of concrete structures in contact to external sulfate solutions requires the definition of a proper diffusion-reaction model, for the computation of the varying sulfate concentration and of the consequent ettringite formation, coupled to a mechanical model for the prediction of swelling and material degradation. In this work, we make use of a two-ions formulation of the reactive-diffusion problem and we propose a bi-phase chemo-elastic damage model aimed to simulate the mechanical response of concrete and apt to be used in structural analyses.